Carbon Emissions Disclosure: Study of Companies Classified as Carbon-Intensive Industries on the Indonesian Stock Exchange - Cintya Salsabilla; Fajri Adrianto; Mohamad Fany Alfarisi (Jurnal Informatika Ekonomi Bisnis, 2024)
This research was created with the aim of seeing whether financial performance, media exposure, managerial ownership, institutional ownership, the audit committee, and the board of commissioners influence carbon emissions disclosure. The object of this research is a company classified as a carbon-intensive industry that is listed on the Indonesian Stock Exchange for the 2019–2022 period. The population in this study includes all companies classified as carbon-intensive industries listed on the Indonesian Stock Exchange for the 2019–2022 period, totaling 142 companies. By using purposive sampling, a total sample of 44 companies was obtained. The information used in this research is secondary information. Secondary data refers to information collected from existing sources. Research data This information was obtained from the official website of the Indonesian Stock Exchange, namely www.idx.co.id and the company's official website. The data needed in this research is the disclosure of carbon emissions for each company in 4 consecutive years from 2019-2022 in each company's sustainability report and annual report. After all the required data and information have been collected, the data processing stage can be carried out. Data processing was carried out using Eviews 12 software.